Categorizing Competence: Consumer debt and the reproduction of gender-based status differences. Issue 9 (September 2018) - Buchanan, Sean; Ruebottom, Trish; Riaz, Suhaib
We examine how gender inequalities are reproduced through categorization processes in mainstream discourse. Drawing from an analysis of six years of US media coverage of credit card borrowers throughout the recent financial crisis, we show how categorization processes facilitate gender-based status differences by categorizing male and female credit card borrowers based on competence. We find that three dimensions of competence—savviness, responsibility, and agency—are constructed through two discursive mechanisms: accounts and vocabularies . Additionally, we highlight how vocabularies work to amplify stereotype-consistent accounts, yet undermine stereotype-inconsistent accounts. We contribute to research on institutional maintenance by highlighting the role of categorization processes in the reproduction of institutionalized relations of inequality. Further, we contribute to research on gender inequality by offering an in-depth examination of the micro-processes involved in the social construction of gender-based status differences. In this way, we shed new light on the cultural means through which gender inequalities are reproduced.